Pengaruh Perendaman Air Perasan Jeruk Lemon dan Asam Cikala Terhadap Kekasaran Permukaan Resin Komposit Nanofiller - Rut Viodetta Sirait; Chandra Susanto; Dian Soraya Tanjung (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; The smooth surface of the nanofiller composite resin can become rough with the consumption of acidic foods/drinks. Objectives; know the difference of the effect of immersion of lemon juice and cikala acid juice on the roughness of the nanofiller composite resin. Method; laboratory experimental research with nanofiller composite resin samples. Statistical test using ANOVA test. Results; showed that there was a significant difference (p <0.05) between the roughness of the nanofiller composite resin soaked in cikala acid juice and the control group but the results showed no significant difference (p> 0.05) between the roughness of the nanofiller composite resin immersed in water. lemon juice with the control group. Conclusion; that there is a significant difference between the effect of soaking water with cikala acid juice and lemon juice on the surface roughness of the nanofiller composite resin